1995
DOI: 10.1007/bf01105794
|View full text |Cite
|
Sign up to set email alerts
|

High affinity IgE receptor (Fc?RI) expression on eosinophils infiltrating the lesions and mite patch tested sites in atopic dermatitis

Abstract: Expression of the high affinity IgE receptor (Fc epsilon RI) on eosinophils has recently been reported. This led us to evaluate Fc epsilon RI expression on eosinophils in atopic dermatitis (AD). Double immunofluorescence stainings with an anti-Fc epsilon RI monoclonal antibody (mAb) and a polyclonal antieosinophil cationic protein (ECP) antibody were performed on lesional biopsy specimens from patients with AD and from patients with bullous pemphigoid (BP) as controls. In AD and BP lesions, 77% and 70% of eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
2
17
1
1
Order By: Relevance
“…[74] In addition to the low-affinity FcεRII, the high-affinity FcεRI is expressed not only on mast cells and basophils, [75] but also on eosinophils. [76] In this line, Messingham et al recently identified FcεRI on peripheral blood and skin eosinophils. [77] Tanaka et al found FcεRI expression in 70% of the eosinophils in lesional BP skin.…”
Section: Eosinophiliamentioning
confidence: 98%
See 1 more Smart Citation
“…[74] In addition to the low-affinity FcεRII, the high-affinity FcεRI is expressed not only on mast cells and basophils, [75] but also on eosinophils. [76] In this line, Messingham et al recently identified FcεRI on peripheral blood and skin eosinophils. [77] Tanaka et al found FcεRI expression in 70% of the eosinophils in lesional BP skin.…”
Section: Eosinophiliamentioning
confidence: 98%
“…[77] Tanaka et al found FcεRI expression in 70% of the eosinophils in lesional BP skin. [76] Binding of anti-BP180 NC16A IgE on these eosinophils might result in eosinophil degranulation or may trigger mast cell degranulation, which has been suggested to be in a piecemeal degranulation pattern [78,79] and therefore might contribute to blister development. In addition, gelatinase derived from eosinophils has been reported to cleave the extracellular domain of BP180.…”
Section: Eosinophiliamentioning
confidence: 99%
“…Human eosinophil IgE receptors include a variant of CD23 (Grangette et al 1989), the low affinity IgE receptor, and on some eosinophils, especially those from patients with allergic diseases, the high affinity FcεRI receptor (Gounni et al 1994b). Both CD23 and FcεRI are detectable on eosinophils in sites of allergic reactions (Tanaka et al 1995, Humbert et al 1996, including the airways (Chihara et al 1989, Humbert et al 1996. In mucosal sites, eosinophils will be present with antibodies of all three classes; and for inhaled allergens, IgG, IgE and IgA antibodies to relevant antigens are measurable in mucosal secretions (Platts-Mills 1979, Kitani et al 1985, Desvaux et al 1989.…”
Section: Other Lymphocyte-eosinophil Interactive Mechanismsmentioning
confidence: 99%
“…In addition to LC, FaRI expression by eosinophils (13) and monocytes (14) was recently reported. Our group demonstrated FaRI expression on eosinophils infiltrating the lesions of AD (15). FceRI aggregation resulted in eosinophil peroxidase release in eosinophils (13) and Ca 2 + influx in monocytes (14).…”
Section: Discussionmentioning
confidence: 97%